Hubungan Pengetahuan tentang Pola Asuh Balita terhadap Keikutsertaan Ibu dalam Kelas Ibu Balita di Desa Pasirtalaga Kecamatan Telagasari Kabupaten Karawang Provinsi Jawa Barat - Sifa Nuriah; Rahmadyanti Rahmadyanti (Universitas Malahayati Lampung, 2024)
ABSTRACT The mother under five class program is a class for mothers who have children aged 0-5 years together for discussions, health nutrition services and stimulation of growth and development guided by the facilitator using the MCH handbook. The impact that can be caused if the execution of toddler mother classes does not go well is the low use of the MCH handbook which will lead to low understanding of mothers about child health. To determine the relationship between knowledge of parenting toddlers, age, education, mother's parity on participation in toddler mothers' classes. The chi-square research design uses questionnaires to be distributed directly to the respondents. Researchers will collect data using a questionnaire. Total population of 82 respondents, using total sampling. Based on statistical tests, it shows that knowledge of Mother Toddler Parenting has a p-value of 0.000 0.05, Age has a p-value of 0.009 0.05, Latest education has a p-value of 0.028 0.05, Productivity has a p-value of 0.000 0.05 and Parity has a p-value of 0.000 0.05. There is a significant relationship between knowledge of mother-to-five parenting, age, last education, productivity and parity towards class participation of mothers of toddlers aged 0-5 years in Pasirtalaga Village, Telagasari District, Kab. Karawang. Keywords: Toddler Mother Class, Knowledge of Toddler Parenting, Age, Education, Parity ABSTRAK Program kelas ibu balita adalah kelas para ibu yang mempunyai anak berusia 0-5 tahun bersama sama berdiskusi, pelayanan kesehatan gizi dan stimulasi tumbuh kembang yang di bimbing oleh fasilitator dengan menggunakan buku KIA. Dampak yang dapat ditimbulkan jika pelaksanaan kelas ibu balita tidak berjalan dengan baik yaitu rendahnya pemanfaatan buku KIA yang akan menyebabkan rendahnya pemahaman ibu terhadap kesehatan anak. Diketahuinya hubungan pengetahuan pola asuh balita, usia, pendidikan, paritas ibu terhadap ke ikutsertaan dalam kelas ibu balita. Desain penelitian chi square dengan rancangan menyebar kuesioner langsung pada responden. Peneliti akan melakukan pengumpulan data menggunakan kuesioner. Total populasi sebanyak 82 responden, menggunakan total sampling. Berdasarkan uji statistik menunjukan bahwa pengetahuan Pola Asuh Ibu Balita memiliki p-value 0,000 0,05, Usia memiliki p-value 0,001 0,05, Pendidikan terakhir memiliki p-value 0,034 0,05, Produktifitas memiliki p-value 0,000 0,05 dan Paritas memiliki p-value 0,000 0,05. Terdapat hubungan yang signifikan antara pengetahuan Pola Asuh Ibu Balita, Usia, Pendidikan Terakhir, Produktifitas dan Paritas tehadap Keikutsertaan Kelas Ibu Balita usia 0-5 Tahun di Desa Pasirtalaga Kecamatan Telagasari, Kab. Karawang. Kata Kunci: Kelas Ibu Balita, Pengetahuan Pola Asuh Balita, Usia, Pendidikan, Paritas